PUB11-Dependent Ubiquitination of the Phospholipid Flippase ALA10 Modifies ALA10 Localization and Affects the Pool of Linolenic Phosphatidylcholine - Salvaing, Juliette; Botella, César; Albrieux, Catherine; Gros, Valérie; Block, Maryse A.; Jouhet, Juliette (Frontiers in Plant Science, 2020)
Biogenesis of photosynthetic membranes depends on galactolipid synthesis, which relies on several cell compartments, notably the endoplasmic reticulum (ER) and the chloroplast envelope. Galactolipid synthesis involves lipid trafficking between both membrane compartments. In Arabidopsis, ALA10, a phospholipid flippase of the P4 type-ATPase family, counteracts the limitation of monogalactosyldiacylglycerol (MGDG) production and has a positive effect on leaf development. ALA10 locates in distinct domains of the ER depending on the ALIS (ALA interacting subunit) subunit it interacts with: close to the plasma membrane with ALIS1, or next to chloroplasts with ALIS5. It interacts with FAD2 (Fatty acid desaturase 2) and prevents accumulation of linolenic (18:3) containing phosphatidylcholine (PC) stimulating an increase of MGDG synthesis. Here we report that ALA10 interacts with PUB11 (plant U-box type 11), an E3 protein ubiquitin ligase, in vitro and in vivo. ALA10 is however ubiquitinated and degraded by the 26S proteasome in a PUB11-independent process. In pub11 null mutant, the proteasome-dependent degradation of ALA10 is retained and ALA10 is still subject to ubiquitination although its ubiquitination profile appears different. In the absence of PUB11, ALA10 is constrained to the ER close to chloroplasts, which is the usual location when ALA10 is overexpressed. Additionally, in this condition, the decrease of 18:3 containing PC is no longer observed. Taken together these results suggest, that ALA10 contributes in chloroplast-distal ER interacting domains, to reduce the 18:3 desaturation of PC and that PUB11 is involved in reconditioning of ALA10 from chloroplast-proximal to chloroplast-distal ER interacting domains.